Effects of seed priming and soil application with silicon on growth, yield and quality of grape tomato under water deficit - Pantamit Saekong; Datta, Avishek; Loc, Thai Nguyen; Anal, Anil K.; The Royal Thai Government; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
In the arid and semiarid area, where the precipitation is insufficient, tomato cultivation is necessarily suffered from water deficit stress. However, silicon has been well documented as beneficial elements for intensifying the plant resistance to serveral biological and environmental stresses, especially drought. For evaluating the ameliorative effect of Si on growth, yield, and fruit quality of grape tomato under water deficit stress, the two experiments were carried out to investigate the effect of doses, and application methods of Sa on grape tomato under water limiting condition. The first experiment was soil application with Sa, which treatments consisted of five Sa levels (0, 75, 150, 300, and 600 kg Sa ha-1) corresponding to three levels of soil water content (50% FC, 75% FC, and 100% FC). For the 2nd experiment, Sa was applied by seed priming, which treatments included five Sa doses of priming solution (0, 0.065, 0.125, 0.25, and 0.5 mM), transplanting under the same soil water content with the first experiment. The result revealed that under moderate drought stress (75% FC), total yield was significantly decreased by approximately 28% and 48% in soil application and priming seed with Sa, respectively. Interestingly, the Sa application irrespective of application methods provided a higher fruit{u2019}s number and total weight of tomato. The result of Sa application either seed priming at 0.25 mM, and soil application at 300 kg Sa ha-1 were more pronounced than other doses, and could be suggested as the optimal doses for cherry tomato T309 hybrid tomato variety cultivated in water limiting condition.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agricultural Systems and Engineering
Thesis (M. Sc.) - Asian Institute of Technology, 2020
Keywords: Plants -- Effect of drought on; Seed treatment; Tomatoes